Cytomorphological Monitoring of the Rate of Healing of Aft and Traumatic Injuries of the Oral Mucosa - Anton Timoshin (Journal of Global Pharma Technology, 2020)
The oral mucosa is an indicator that shows the state and functioning of internal organs and systems of the entire body. Inflammatory diseases of the oral mucosa are a pathology that affects patients of various ages. And it causes some discomfort to the patient and disrupts the usual rhythm of life. With a long course of this pathology, there is a violation of the endocrine glands, the immune system, and against the background of a painful symptom, psycho emotional tension may occur. The inflammatory process on the oral mucosa can be caused by factors such as bacterial, viral, fungal, and others. Regardless of the etiological factor, the inflammatory process itself does not pose a threat to the patient's life, even in spite of the etiological factor, although it complicates it. However, in the absence of treatment and prolonged course, it can lead to malignancy of the process. This is facilitated by the constant impact on the pathological focus of mechanical, chemical and thermal stimuli when eating. Also, if the patient has chronic somatic diseases that occur against the background of a decrease in immunological protection, the threat increases. Keywords: Oral mucosa, Inflammation, Pathology, Farmadont III.